Complement anaphylatoxin C3a is a potent inducer of embryonic chick retina regeneration - Haynes, Tracy (Nature Pub. Group, 2013)
Identifying the initiation signals for tissue regeneration in vertebrates is one of the major challenges in regenerative biology. Much of the research thus far has indicated that certain growth factors have key roles. Here we show that complement fragment C3a is sufficient to induce complete regeneration of the embryonic chick retina from stem/progenitor cells present in the eye, independent of fibroblast growth factor receptor signaling. Instead, C3a induces retina regeneration via STAT3 activation, which in turn activates the injury- and inflammation-responsive factors, IL-6, IL-8 and TNF-α. This activation sets forth regulation of Wnt2b, Six3 and Sox2, genes associated with retina stem and progenitor cells. Thus, our results establish a mechanism for retina regeneration based on injury and inflammation signals. Furthermore, our results indicate a unique function for complement anaphylatoxins that implicate these molecules in the induction and complete regeneration of the retina, opening new avenues of experimentation in the field.